The relationship between home bias and globalization – an international comparison. Issue 2 (15th October 2020) - Riff, Sivan; Yagil, Yossi
Abstract : Purpose: The authors aim to examine the relationship between home bias and globalization while specifically examining the effects of the different dimensions of globalization (social, economic and political) for both developed countries and developing countries. Additionally, the authors test the effect of globalization regulation and laws against actual globalization activities. Design/methodology/approach: This study investigates the influence of globalization on the home bias phenomenon using a panel regression and a three-dimensional globalization index (social, economic and political globalization) of 42 developed and developing countries from 2001 to 2016. Findings: The results show that globalization significantly reduces home bias. In addition, the authors find that social globalization has a key influence compared to economic globalization and that political globalization has the weakest effect. For developing economies only, economic globalization as well as globalization laws and regulations have a crucial impact on the level of home bias. Originality/value: Prior studies focus merely on the aspect of financial integration. Our study provides a more comprehensive outlook by distinguishing between the features of globalization (social, economic and political) as well as the actual globalization activities (de facto) compared to the laws and regulations enabling those actives (de jure). Lauterbach and Reisman (2004) show that globalization reduces home bias through a theoretical model. This study provides empirical merit to their work. In addition, we examine the different aspects of globalization for both emerging and developed markets.